Question: Removing x From Set A

Comment on Removing x From Set A

Sum1 = MN
Sum2 = (M-3) (N-1)

sum2 = MN - 3N - M + 3
Sum2 = Sum1 - 3N - M + 3

since Sum1 is greater that Sum2

Sum1 - Sum2 = 3N + M - 3
LHS gives removed value that is X

X = 21 - 3
X = 18.

I think I figured out an easier way to do this:

1) Sum = (mean)(n) --> Sum = MN
2) Sum - x = (M-3)(N-1)

Substitute 1) into 2):
MN - x = (M-3)(N-1)
MN - x = MN - M - 3N + 3
- x = - M - 3N + 3
x = M + 3 N - 3
x = (21) - 3
x = 18
greenlight-admin's picture

Perfect!

Have a question about this video?

Post your question in the Comment section below, and Brent (the course creator) will answer it as fast as humanly possible.

Change Playback Speed

You have the option of watching the videos at various speeds (25% faster, 50% faster, etc). To change the playback speed, click the settings icon on the right side of the video status bar.

Let me Know

Have a suggestion to make the course even better? Email me today!

Free “Question of the Day” emails!